2005
DOI: 10.1108/01437730510624566
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of emotion expressiveness: gender differences among senior executives

Abstract: Purpose -Folk theory and empirical studies generally indicate that women tend to be somewhat more expressive than men. The present study seeks to determine whether there are gender-related emotion-expressiveness differences among senior executives and to explore the extent to which there are emotion expressiveness differences by organizational position. Design/methodology/approach -The levels of self-reported expressiveness among senior organizational leaders (781 males, 669 females) were examined. Differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…In contrast to the trait approach, behavioral approach states that people can learn the characteristics of a leader (Ivancevich et al, 2011). Earliest behavioral approach concluded that effective leadership practices both task oriented and people oriented (Callahan et al, 2005). Finally, the contingency approach of leadership suggests that the appropriate style of leadership tend to vary according to the situational.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the trait approach, behavioral approach states that people can learn the characteristics of a leader (Ivancevich et al, 2011). Earliest behavioral approach concluded that effective leadership practices both task oriented and people oriented (Callahan et al, 2005). Finally, the contingency approach of leadership suggests that the appropriate style of leadership tend to vary according to the situational.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, the contingency approach of leadership suggests that the appropriate style of leadership tend to vary according to the situational. In other words, contingency approach has to do with the principle that an effective leader is affected by the situation (Callahan et al, 2005). Path-goal theory focused more on providing enabling conditions for subordinate success and less on the situation or leader behavior (House, 1971).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the linguistic perspective, we examine the nature of swearing and its relevance in society. We explore varying norms across gender, occupation, and seniority (see Callahan et al, 2005, for gender leadership differences).…”
Section: Theory Developmentmentioning
confidence: 99%
“…A traditionally held norm implies that women tend to use a more prestigious style of speech than men, and avoid swearing (Jespersen, 1922). Other norms indicate the higher tendency of male leaders to be expressive (Callahan et al, 2005). However, it is wrong to simply position speech styles into two mutually exclusive groups by gender (Hughes, 1992;Stapleton, 2003).…”
Section: Gender and Swearingmentioning
confidence: 99%
“…The authors further argued that women struggle to balance the need to display respectability with being considered 'woman enough' (Mavin & Grandy, 2016). This notion of having to balance external expectations with one's 'woman-ness' is something that many researchers discuss in relation to the experience of being a woman leader (Catalyst, 2007;Callahan et al, 2005;Eagly & Carli, 2007;Vasavada, 2012).…”
Section: Influence Of Gendermentioning
confidence: 99%